The Essence of Context of an Organization in Approach to Management Systems - Matuszak-Flejszman, Alina; Pochyluk , Robert (Studia Oeconomica Posnaniensia, 2016)
New editions of the International Standards ISO 9001 and ISO 14001, which were published in September 2015, introduce a new requirement for determining the context of an organization. Therefore, representatives of many organizations wonder about the interpretation of this requirement, because they are afraid that they will have a problem with defining the context of the organization and the determination of the stakeholders related to internal and external environment of the organization. This article attempted to define the context of an organization resulting from the new standards ISO 9001 and ISO 14001 and provide relevant examples. The authors sought to identify how to determine the context of the organization in business practice taking into account various external and internal issues. The study was conducted based on the literature analysis, as well as on the basis of the experience of the authors as consultants and auditors of management systems. The aim of the article is to point out the importance of the implementation and maintenance of the system quality and environmental management, and also to define the context of the organization and understanding of the needs and expectations of stakeholders. It was hypothesized that determining the context of an organization requires a detailed knowledge of all the processes carried out by an organization and its environmental aspects and associated environmental impacts, as well as the external factors affecting an organization in any means, and it is of fundamental value for planning an environmental management system. Thus, the term "context of an organization" requires involving a number of employees representing various areas of business, including a product or service life cycle. The article provides examples of stakeholders, both in the quality management system and environmental management system. Moreover, the role of the scope of the management system resulting from the context of an organization as well as to the structure of the management system based on a process approach and four steps Deming’s approach (PDCA).